Utilizing BPS Statistical Data Technology to Support Development Planning in Bengkulu City - Novella Firsty Putri Diantara; Aisha Tri Chayati; Putri Ghea Natasya; Vianos Alhado; Farida Nur Aini (LP3M KH Yazid Karimullah Institute, 2026)
This study aims to analyze the utilization of statistical data technology provided by the Central Statistics Agency (BPS) in supporting the regional development planning process in Bengkulu City. The study employed a descriptive qualitative approach using literature review, documentation, observation, and interviews as research methods. Research data were obtained from official BPS publications, regional development planning documents, government regulations, and various relevant scientific literatures. The findings indicate that BPS statistical data technology plays an important role in supporting evidence-based planning through the provision of accurate, up-to-date, and digitally accessible data. Statistical data are utilized for identifying development issues, determining policy priorities, preparing planning documents such as the Regional Medium-Term Development Plan (RPJMD) and the Regional Government Work Plan (RKPD), allocating budgets, as well as conducting monitoring and evaluation of regional development programs. The digitalization of statistical services has also improved efficiency, transparency, and accountability in regional governance. However, the utilization of statistical data technology still faces several challenges, including the lack of optimal data integration among institutions, limited interoperability of information systems, differences in data management standards, and limited human resource capacity in data management and analysis. Therefore, strengthening the capacity of government personnel, improving information technology infrastructure, implementing the One Data Indonesia policy, and enhancing collaboration between BPS and local governments are necessary to optimize the use of statistical data in supporting effective, efficient, transparent, and sustainable development in Bengkulu City